Employee Perception of Digital Well-Being: A Study on Generation Z In Indonesia's Big Cities - Affan, Mohammad Romdhon; Iswanto, Dedy; Fuzail, Muhammad (SCIENTIA: Journal of Multi Disciplinary Science, 2025)
Employee well-being has become a strategic aspect of human resource management as it affects workforce performance, engagement, and retention. In the digital era, organizations are increasingly adopting technology-based wellness programs to respond to the dynamic needs of employees, especially Generation Z, known as digital natives. This generation demands flexibility, work-life balance, and attention to mental health through an easily accessible and personalized platform. In Indonesia's major cities such as Jakarta, Bandung, and Surabaya, the challenges of urbanization, work stress, and technological penetration reinforce the urgency of implementing digital welfare programs. However, research on Gen Z's perception of the effectiveness, ease of use, and value of these programs is still limited. This study aims to systematically review the literature to identify trends, challenges, and unmet needs in the implementation of digital health programs among Generation Z employees in urban areas of Indonesia. The results of this review are expected to provide a basis for the development of more adaptive, inclusive, and sustainable HR strategies in supporting the digital health of the younger generation in the modern workplace.